Analysis of the Relationship Between Sleep Quality and Hypertension Levels in the Elderly: A Study in Pejeng Tampaksiring Village - Mayuni, Anak Agung Risma; Saraswati, Putu Ayu Sita; Wahyuni, Nila; Putra, I Putu Yudi Pramana (Bachelor and Profession of Physiotherapy Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2024)
Introduction: Individuals aged 60 years and above, defined as the elderly, undergo physical and neurological changes due to degenerative processes, often associated with health problems. The risk of hypertension is common among the elderly due to their tendency to have high blood pressure. One factor contributing to hypertension is sleep quality, defined by how well a person sleeps and is characterized by feelings of freshness and vigour upon waking. Methods: An observational analytic study with a cross-sectional approach was chosen for this research. The sampling technique used was purposive sampling. A total of 98 older women were obtained through Lemeshow's sample calculation. Data collection included measuring the sleep quality of the elderly using the Indonesian version of the Pittsburgh Sleep Quality Index (PSQI) questionnaire and measuring hypertension levels using a sphygmomanometer and stethoscope. Results: Hypothesis analysis using Spearman's rho test showed a significant relationship between sleep quality and hypertension levels among the elderly in Pejeng Tampaksiring Village, with a p-value of 0.000 (<0.05). Conclusion: It can be concluded that there is a significant relationship between sleep quality and hypertension levels among the elderly in Pejeng Tampaksiring Village. Keywords: sleep quality, hypertension levels, elderly